Irish Convict Transportation and the Reach of the State in Late Hanoverian Britain - Devereaux, Simon (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractThe difficulties encountered by English authorities in resuming the regular and effective transportation of convicts overseas between the loss of the original American destination in 1775 and the opening of a penal settlement in New South Wales in 1787 are well known to historians of criminal justice. Far less so is the contemporaneous convict crisis in Ireland. This article considers the practice of convict transportation from Ireland throughout the eighteenth century. In particular, it examines a series of three dramatic incidents of the late 1780s in which Irish convicts were unscrupulously (though not illegally) abandoned in Cape Breton, Newfoundland and the Leeward Islands. It argues, first, that such practices were not entirely surprising given the great difficulties that had often been experienced in transporting convicts from Ireland even before 1775. It goes on to suggest that the subsequent decision of authorities in London to assume a directive role in the transportation of Irish convicts was informed by changing perceptions of the British state in both its national and imperial dimensions.